PERENCANAAN MANAJEMEN PROYEK KONSTRUKSI PADA KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN KABUPATEN KETAPANG: PERENCANAAN MANAJEMEN PROYEK KONSTRUKSI PADA KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN KABUPATEN KETAPANG - utami, sonia; Arianti, iin; Konstatinus, ayub; Cahyani, yasnita (Jurusan Teknik Sipil Polnep, 2021)
Ketapang Regency is one of the areas that has a considerable influence on the socio-economicdevelopment of the community, especially sea transportation. In facilitating the supervision of theentry and exit of sea transportation at the port of Ketapang Regency, it is necessary to build theHarbormaster Office and the Port Authority. In the construction of the Ketapang RegencyHarbormaster and Port Authority Office, it is necessary to have good and correct planning in terms oftime, cost, quality, human resources, and an environmental occupational safety and healthmanagement system so that the project can be completed on time and efficiently. The method used inthe management of this Construction Project is the SNI method covering five aspects, namely costmanagement in the form of a budget plan, time management in the form of a barchart, S curve andnetwork planning, human resource management in the form of labor requirements, qualitymanagement in the form of a work plan of requirements. requirements and management systems foroccupational safety and health in the form of the number of personal protective equipment required.The costs needed for the construction of the Kesyahbandaran Office and the Port Authority ofKetapang Regency are 9,129,893,000.00 within a period of 24 weeks 180 calendar days, with aworkforce requirement of 113 workers per week, a work plan with conditions as a reference, as wellas 78 pieces of personal protective equipment needed.